The Ethnography of Communication with Special Reference To Indonesian-English Translation of Lontar Tantri Carita - Arnita Yanti, Ni Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2017)
This study sets out to determine figurative language translated from the source language (Indonesian Language) and its translation on the target language (English Language) in terms of utterance and sentences. The data on this paper were obtained from reading a book entitled Lontar Tantri Carita (Kawi-Indonesia-Inggris) written by I Gusti Ayu Srinatih,et al. The method of collecting data used in this study was observation. Observation method included some techniques such as note taking and continued by arranging data into figurative language classifications. Data that was collected was classified based on the Figurative Language classifications by Larson (1998) and it were analyzed by Ethnography of Communication Theory (Hymes, 1975). The data was presented in qualitative descriptive.  There were more than one figurative language found in the utterance of this book such as Simile, Idiom and Hyperbole. Each of those classifications was also supported by the description of Ethnography of Communication theory